Cognitive, social, and mental health functions of refugee children – screening and supportive actions at school: a study protocol - Oskari Lahtinen; Samuli Kangaslampi; Sanni Aalto; Joosu Soosalu; Kirsi Peltonen (BMC Psychology, 2024)
Abstract Background Despite a world-leading educational system, an achievement gap in educational outcomes exists between children of refugee background and native-born peers in Finland. To offer targeted support for children at schools, we need to be able to reliably assess and understand the interplay of the aspects of children’s cognitive, social, and mental health functions that may explain the underachievement of refugee children. This study tests a novel research-based, universally applicable screening battery for evaluating cognitive, social, and mental health functioning of children at schools and planning supportive actions. It aims to answer research questions about a) the cognitive, social, and mental health functioning of refugee children compared with non-refugee immigrant and native-born children, b) the interplay of these different functions among refugee and other children, c) whether implementing a screening battery can inform schools in planning supportive actions for (refugee) children, and d) whether such supportive actions result in improvements in cognitive, social, and mental health functioning. Methods Four hundred fifty children aged 10–12 will be recruited from primary schools, including 150 children of refugee background, 150 of non-refugee immigrant background, and 150 native-born Finnish children. A screening battery including tasks and questionnaires on different aspects of cognitive, social, and mental health functioning will be used to assess the children in their classrooms at the start and end of a school year. Supporting information will also be collected from parents and teachers. The information gathered will be collated into class-level feedback reports for teachers and, with parental permission, individualized reports for multiprofessional student welfare bodies, for informing supportive actions. Correlational and latent profile analyses, ANOVAs, and linear regression will be used to answer the research questions. Discussion This study will help clarify how the interplay of cognitive, social, and mental health factors may explain underachievement at school among refugee children. It will provide evidence about the extent to which a standardized screening battery could be helpful in informing and planning supportive actions for children at schools, and whether such supportive actions can lead to positive cognitive, social, or mental health outcomes. Trial registration The study will be preregistered on the Open Science Framework.